THE ROLE OF CHRISTIAN EDUCATION IN SUPPORTING INDONESIA'S FREE NUTRITIOUS MEALS POLICY TO PROMOTE HEALTH AND INTELLECTUAL GROWTH - Zalukhu, Amirrudin (Publisher: Bethel Press; Unit Penerbit: STT Bethel Indonesia Jakarta, 2025)
This qualitative study explores the role of Christian education in supporting Indonesia's Free Nutritious Meals Policy (FNMP) to promote children's health and intellectual growth. Using a literature review approach, the research examines existing studies, government reports, and educational frameworks to understand how Christian education complements the policy's goals. The FNMP, which aims to address malnutrition and enhance educational outcomes, provides free meals to students across the country. Christian education, with its emphasis on moral, spiritual, and intellectual development, aligns with the policy by fostering values of stewardship, responsibility, and care for others. This study investigates how Christian schools integrate nutrition education into their curricula and encourage healthy lifestyle choices among students. By examining the intersection of Christian values and national health policies, the paper highlights how Christian education can contribute to raising awareness of the importance of nutrition for physical and cognitive well-being. The research also identifies opportunities for collaboration between Christian institutions and government bodies to strengthen the policy's impact. The findings suggest that Christian education plays a crucial role in not only supporting the FNMP but also enhancing its effectiveness by promoting a well-rounded approach to children's development.